Proposal for new selection criteria considering pre‐transplant muscularity and visceral adiposity in living donor liver transplantation. Issue 2 (17th February 2018) - Hamaguchi, Yuhei; Kaido, Toshimi; Okumura, Shinya; Kobayashi, Atsushi; Shirai, Hisaya; Yao, Siyuan; Yagi, Shintaro; Kamo, Naoko; Okajima, Hideaki; Uemoto, Shinji
Abstract: Background: The significance of pre‐operative body composition has recently attracted much attention in various diseases. However, cut‐off values for these parameters remain undetermined, and these factors are not currently included in selection criteria for recipients of living donor liver transplantation (LDLT). Methods: Using computed tomography of 657 donors for LDLT, skeletal muscle mass, muscle quality, and visceral adiposity were evaluated by using skeletal muscle mass index (SMI), intramuscular adipose tissue content (IMAC), and visceral‐to‐subcutaneous adipose tissue area ratio (VSR). Sex‐specific cut‐offs for SMI, IMAC, and VSR were determined, and correlations with outcomes after LDLT in 277 recipients were examined with the aim of establishing new selection criteria for LDLT. Results: On the basis of younger donor data, we determined sex‐specific cut‐off values for low SMI, high IMAC, and high VSR (mean ± 2 standard deviations). Patients with all three factors showed the lowest survival rate after LDLT (1 year survival rate, 41.2%; P < 0.001). On multivariate analysis, low SMI ( P = 0.002), high IMAC ( P = 0.002), and high VSR ( P = 0.001) were identified as independent risk factors for mortality after LDLT. Based on these findings, we have excluded patients showing all three factors (low SMI, high IMAC, and high VSR) as candidates for LDLT since October 2016. Conclusions: Using cut‐off values determined from healthy donors, we have established new selection criteria for LDLT including body composition, which should improve post‐transplant outcomes.